Evaluation of BAG3 levels in healthy subjects, hypertensive patients, and hypertensive diabetic patients. Issue 3 (25th August 2017) - Derosa, Giuseppe; Maffioli, Pamela; Rosati, Alessandra; M, De Marco; Basile, Anna; D'Angelo, Angela; Romano, Davide; Sahebkar, Amirhossein; Falco, Antonia; Turco, Maria C.
Abstract : BAG3 is a member of human BAG (Bcl‐2‐associated athanogene) proteins and plays a role in apoptosis, cell adhesion, cytoskeleton remodeling, and autophagy. The aim of this study was to evaluate BAG3 levels in healthy subjects, hypertensive patients, and hypertensive diabetic patients. We enrolled 209 Caucasian adults, of both sex, 18–75 years of age, 77 were healthy controls, 62 were affected by hypertension, and 70 were affected by hypertension and type 2 diabetes. All patients underwent an assessment that included medical history, physical examination, vital signs, a 12‐lead electrocardiogram, measurements of systolic (SBP), and diastolic blood pressure (DBP), heart rate (HR), fasting plasma glucose (FPG), glycated hemoglobin (HbA1c ), triglycerides (TG), transaminases, high sensitivity C‐reactive protein (Hs‐CRP), and BAG3. We observed higher blood pressure values in hypertensive, and hypertensive diabetic patients compared to controls. As expected, FPG and HbA1c were higher in diabetic hypertensive patients, compared to the other two groups. No Tg levels differences were recorded among the three groups. Hs‐CRP was higher in diabetic hypertensive patients compared to healthy subjects. Finally, BAG3 levels were higher in hypertensives, and hypertensive diabetic patients compared to controls. We observed higher levels of BAG3 in hypertensive patients compared to healthy controls, and even higher levels in hypertensive diabetic patients compared to healthy subjects. This paper could be the first of a long way to identify potential involvement of deregulated BAG3 levels in cardiometabolic diseases. Abstract : BAG3 is a member of human BAG (Bcl‐2‐associated athanogene) proteins and plays a role in apoptosis, cell adhesion, cytoskeleton remodeling, and autophagy.